Crocins for Ischemic Stroke: A Review of Current Evidence - Shahbaz, Kiran; Chang, Dennis; Zhou, Xian; Low, Mitchell; Seto, Sai Wang; Li, Chung Guang (Frontiers in Pharmacology, 2022)
Crocins (CRs) and related active constituents derived from Crocus Sativus L. (Saffron) have demonstrated protective effects against cerebral ischemia and ischemic stroke, with various bioactivities including neuroprotection, anti-neuroinflammation, antioxidant, and cardiovascular protection. Among CRs, crocin (CR) has been shown to act on multiple mechanisms and signaling pathways involved in ischemic stroke, including mitochondrial apoptosis, nuclear factor kappa light chain enhancer of B cells pathway, S100 calcium-binding protein B, interleukin -6 and vascular endothelial growth factor-A. CR is generally safe and well-tolerated. Pharmacokinetic studies indicate that CR has poor bioavailability and needs to convert to crocetin (CC) in order to cross the blood-brain barrier. Clinical studies have shown the efficacy of saffron and CR in treating various conditions, including metabolic syndrome, depression, Alzheimer’s disease, and coronary artery disease. There is evidence supporting CR as a treatment for ischemic stroke, although further studies are needed to confirm their efficacy and safety in clinical settings.